Motivation, Satisfaction, and Risks of Operational Forces and Helpers Regarding the 2021 and 2013 Flood Operations in Germany - Alexander Fekete (MDPI AG, 2021)
Pluvial floods claimed more than 180 lives in Germany in July 2021, when a large and slow-moving storm system affected Germany and many neighbouring countries. The death tolls and damages were the highest since 1962 in Germany, and soon after, the crisis management was under public critique. This study has undertaken an online survey to understand crisis management better and identify lessons to learn. It has received a positive interest among operational relief forces and other helpers (n = 2264). The findings reveal an overall satisfaction with the operation in general as well as personal lessons learned. It also reveals shortcomings in many areas, ranging from information distribution, coordination, parallel ongoing COVID-19 pandemic, infrastructure resilience, and other factors. Just as well, areas for improvement of the crisis management system are suggested by the respondents. Cooperation and support by the affected population are perceived as positive. This helps to inform other areas of research that are necessary, such as studies on the perception by the affected people. The gaps in assessments of operational forces and some methodological constraints are discussed to advance future follow-up studies.